High Dosage Metolazone in Chronic Renal Failure. Issue 5834 (28th October 1972) - Dargie, H. J.; Allison, Marjorie E. M.; Kennedy, A. C.; Gray, Mary J. B.
Abstract : Metolazone is a modified quinazolinesulphonamide and in a dose of between 4 and 7·5 mg is an effective diuretic in man with normal renal function. Fourteen patients with non-oedematous stable chronic renal failure (creatinine clearance ranging from 1·2 to 12 ml/min) were given metolazone in doses ranging from 20-150 mg. A noticeable increase in urine flow and sodium excretion occurred, free water clearance increased, and there was a small but significant increase in potassium excretion. No side effects were noted.